MENINGKATKAN KINERJA ALAT PENGUJIAN KUAT TEKAN BETON DI LABORATORIUM UJI BAHAN DEPARTEMEN TEKNIK SIPIL DAN PERENCANAAN UNIVERSITAS NEGERI MALANG - Ardian Purba Sasangka; Mohammad Musthofa Al Ansyorie; Muhammad Muchlis (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract Director General of Housing Provision of the Ministry of PUPR, Khalawi Abdul Hamid said that the data on house construction recorded in the One Million House program in January 2019 reached 77,326 housing units (Hardum, 2019). In relation to the implementation of the construction mentioned above, the quality of building materials is needed that can support building conditions according to standards, so that a sturdy building with good concrete quality will be produced. In the process of testing concrete quality in the Material Test Laboratory of the Department of Civil Engineering and Planning, State University of Malang, a standard concrete compressive strength test equipment is needed, namely a concrete quality test equipment (compressive strength) that produces measuring values digitally, so that test results with a very accurate loading control level are obtained for quality testing resulting in constant and accurate loading and readings. Conversely, the condition of concrete quality testing equipment (compressive strength) in the Material Test Laboratory of the Department of Civil Engineering and Planning, State University of Malang still found several concrete compressive strength test equipment that still use the Analog Model Compression Testing Machine. The performance of the tool is manual, relying on manual observation that is less precise and the working function of the tool and reading the test result data is still manual, so that it is necessary to improve the performance of analog concrete compressive strength testing equipment into digital testing equipment at the Materials Test Laboratory of the Department of Civil Engineering and Planning, State University of Malang by modifying analog test equipment, adding a series of electronic sensors, pressure transmitters that connect analog machines with electronic test result reading devices, so that digital reporting of test result data will be obtained. Abstrak Direktur Jenderal Penyediaan Perumahan Kementerian PUPR, Khalawi Abdul Hamid mengatakan bahwa data pembangunan rumah yang tercatat dalam program Satu Juta Rumah pada Januari 2019 angkanya mencapai 77.326 unit rumah (Hardum, 2019). Dalam kaitannya dengan pelaksanaan pembangunan tersebut diatas diperlukan kualitas bahan bangunan yang dapat menunjang kondisi bangunan sesuai standart, sehingga akan dihasilkan bangunan yang kokoh dengan kualitas beton yang baik. Pada proses pengujian kualitas beton dalam Laboratorium Uji Bahan Departemen Teknik Sipil dan Perencanaan Universitas Negeri Malang diperlukan kondisi alat uji kuat tekan beton yang standart, yaitu alat uji kualitas beton (kuat tekan) yang menghasilkan nilai ukur secara digital, sehingga didapatkan hasil pengujian dengan tingkat kendali pembebanan yang sangat akurat untuk pengujian berkualitas menghasilkan pembebanan dan pembacaan yang konstan dan akurat. Sebaliknya, kondisi alat uji kualitas beton (kuat tekan) yang ada di Laboratorium Uji Bahan Departemen Teknik Sipil dan Perencanaan Universitas Negeri Malang masih didapati beberapa alat uji kuat tekan beton yang masih menggunakan Mesin Uji Kompresi Model Analog. Kinerja alat bersifat manual, dengan mengandalkan pengamatan secara manual yang kurang teliti dan fungsi kerja alat dan pembacaan data hasil uji masih bersifat manual, sehingga diperlukan peningkatan kinerja alat pengujian kuat tekan beton analog menjadi alat uji digital di Laboratorium Uji Bahan Departemen Teknik Sipil dan Perencanaan Universitas Negeri Malang dengan cara memodifikasi alat uji analog ditambahkan rangkaian sensor elektronik pressure transmitter yang menghubungkan mesin analog dengan perangkat pembaca hasil uji secara elektronik, sehingga akan didapatkan pelaporan data hasil uji secara digital.